The probiotic L. casei LC-XCAL™ improves metabolic health in a diet-induced obesity mouse model without altering the microbiome. Issue 1 (9th November 2020) - Walsh, Calum J.; Healy, Selena; O'Toole, Paul W.; Murphy, Eileen F.; Cotter, Paul D.
ABSTRACT: Chronic low-grade inflammation associated with obesity may be a target for improvement of metabolic health. Some exopolysaccharide (EPS)-producing bacteria have been shown to have anti-inflammatory effects in gastrointestinal inflammatory conditions. However, evidence for the role of EPS-producing probiotics in the management of obesity and associated conditions is scarce and the role of the microbiota is unclear. In this study, two probiotic candidates were screened for their effects on metabolic health using the diet-induced obesity (DIO) mouse model. Mice fed a high-fat diet supplemented with the anti-inflammatory, EPS-producing strain L. casei LC-XCAL ™ showed significantly reduced hepatic triglycerides, hepatic total cholesterol, and fat pad weight compared to those fed a high-fat diet alone, likely as a result of reduced energy absorption from food. 16-S rRNA amplicon analysis of the fecal microbiota of these mice indicated that the altered metabolic phenotype as a result of the L. casei LC-XCAL strain administration was not associated with an overall change in the composition or inferred functional capacity of the fecal microbiota despite some abundance changes in individual taxa and functions. These findings provide evidence that specific microbial strategies can improve metabolic health independent of the microbiome and reinforce the importance of carefully selecting the most appropriate strain for specific indications by thorough screening programmes.